Pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), dan Return on Assets (ROA) terhadap Harga Saham: (Studi pada Perusahaan Manufaktur Subsektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2023) - Rahmayani, Tania; Sjarif, Devyanthi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to examine the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on stock prices of consumer goods sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2023. The approach used is quantitative with verification and descriptive methodology. Secondary data is taken from financial reports on the Indonesia Stock Exchange and related company websites. The purposive sampling technique produced a sample of 10 companies out of 36 companies. Data was collected through documentation and literature review, then analyzed using descriptive and verification analysis. The results of the t-test show that CR has a significant effect on stock prices. DER significantly affects stock prices, and ROA has no significant impact on stock prices. The F test confirms the significant regression model. These findings indicate that stock prices are more influenced by the company's capital structure (DER) and liquidity (CR) than asset utilization efficiency (ROA). These results provide valuable insights for investors and company managers about the financial factors that must be considered in stock pricing decisions